'I think autism is like running on Windows while everyone else is a Mac': using a participatory action research approach with students on the autistic spectrum to rearticulate autism and the lived experience of university. Issue 2 (15th March 2017) - Vincent, Jonathan; Potts, Megan; Fletcher, Daniel; Hodges, Simon; Howells, Jenny; Mitchell, Alex; Mallon, Brett; Ledger, Thomas
Abstract: This co-authored article outlines the research process and key findings from the Stratus Writers Project, a participatory action research project with a group of seven students on the autistic spectrum at a university in the North of England. The project explores their experiences of university through critical autobiographies and offers unique insider perspectives into some of the key issues, challenges and successes. Building on a participatory action research approach, the data were collected by the participants themselves; however, this study departs from traditional research in that the participants also analysed the data, thus offering rich and potentially overlooked theoretical knowledge. The article concludes by demonstrating the strength of participatory action research approaches by identifying the impact that our project and its findings have had so far.